2020
DOI: 10.1111/jar.12812
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and needs of direct support staff working with people with intellectual disabilities during the COVID‐19 pandemic: A thematic analysis

Abstract: Background The present study aimed to explore the experiences and needs of direct support staff during the initial stage of the COVID‐19 lockdown in the Netherlands. Method Overall, eleven direct support staff were recruited from five intellectual disability services to participate in this descriptive qualitative study. They recorded 34 audio messages during the considered period. Thematic analysis was used to analyse these audio recordings. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 22 publications
2
85
0
4
Order By: Relevance
“…This extra time also afforded the chance to support the person to express their preferences and increase control over the range of choices that were available to them. The need for social care staff to be creative and problem solve in the face of COVID‐19 restrictions was also highlighted in the research by Embregts et al (2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This extra time also afforded the chance to support the person to express their preferences and increase control over the range of choices that were available to them. The need for social care staff to be creative and problem solve in the face of COVID‐19 restrictions was also highlighted in the research by Embregts et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…In respect of the impact on social care staff, Embregts et al (2020) conducted a small qualitative study with 11 care staff in the Netherlands and found that the staff reported both positive and negative effects of COVID‐19. They had concerns about becoming infected and expressed frustration that their role and the vulnerable position of people with an intellectual disability were largely overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from administrative data may be most useful for starting conversations with clients and staff close to the source of these data (Wolpert and Rutter 2018), helping to put their unique experiences and challenges during this pandemic (e.g., Embregts et al . in press‐a, b) on the agenda and into a wider perspective. Clients have been found to attribute challenging behaviours to a range of situational and social factors (Van den Bogaard et al .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the restrictions are likely to cause increased confusion and distress for many people with an intellectual disability (Grier et al, 2020). There has also been some research indicating the negative impact on the mental health, forward planning and coordination tasks of social care staff working under these circumstances (Embregts et al, 2020). In combination, this may result in increases in behaviours that challenge (Courtenay & Perera, 2020).…”
Section: Mckenzie Et Almentioning
confidence: 99%